Breath biopsy biomarkers: cell-free nucleic acids in exhaled breath condensate - Pös, Ondrej; Styk, Jakub; Kubanova, Monika; Bokorova, Silvia; Buglyo, Gergely; Soltesz, Beata; Lukasz, Peter; Benes, Vladimir; Repiska, Vanda; Nagy, Balint; Szemes, Tomas (Frontiers in Medicine, 2025)
Exhaled breath condensate (EBC) has emerged as a promising, organ-specific biofluid for non-invasive molecular diagnostics. While breath analysis has traditionally focused on volatile organic compounds (VOCs), recent advances have shifted attention toward non-volatile constituents, particularly cell-free nucleic acids (cfNAs) such as genomic DNA, mitochondrial DNA, mRNA, miRNA, long non-coding RNA, and microbial genetic material. These molecules reflect the respiratory tract biology and can serve as biomarkers for a range of clinical conditions, including lung cancer, obstructive lung diseases, infections, and potentially even systemic disorders. This review summarizes the current knowledge on cfNAs in EBC, highlighting technical challenges in sample collection and nucleic acid extraction. We provide a comparison of EBC collection devices, discuss optimization strategies for nucleic acid recovery, and examine emerging applications such as early cancer detection, treatment monitoring, infection diagnostics, and endotyping of chronic airway diseases. The feasibility of at-home EBC sampling with portable collection devices offers additional advantages, potentially overcoming logistical and psychological barriers that often delay clinical care. Although limitations remain, including low cfNA yield and lack of standardization, ongoing innovation in sampling and molecular techniques is rapidly expanding the translational potential of breath biopsy. With further development, EBC-based cfNA profiling may complement blood-based liquid biopsies and, in specific contexts such as lung cancer, provide additional organ-specific information.